Weedy rice (Oryza sativa) II. Response of weedy rice to seed burial and flooding depth - Chauhan, Bhagirath Singh (Cambridge University Press, 2012)
Weedy rice is a serious problem of cultivated rice in most of the rice-growing areas in Asia, causing increased production costs and yield losses in rice. A study was conducted to determine the response of weedy rice accessions from India (IWR), Malaysia (MWR), Thailand (TWR), and Vietnam (VWR) to seed burial and flooding depths. The greatest emergence for each weedy rice accession (97% for IWR, 82% for MWR, 97% for TWR, and 94% for VWR) was observed in seeds placed on the soil surface. Seedling emergence decreased with increase in burial depth. For the IWR accession, 0.5% of the seedlings emerged from 8-cm depth, whereas for the other three weedy rice accessions, no seedlings emerged from this depth. When seeds were sown on the soil surface, flooding depth ranging from 0 to 8 cm had no or very little effect on seedling emergence of different weedy rice accessions. On the other hand, flooding decreased seedling emergence in all weedy rice accessions when seeds were sown at 1 cm deep into the soil. Compared with seedling emergence, flooding had a more pronounced effect on seedling biomass for all weedy rice accessions. A flooding depth of 2 cm reduced seedling biomass by an amount greater than 85% of each weedy rice accession. The results of this study suggest that emergence and growth of weedy rice could be suppressed by deep tillage that buries seeds below their maximum depth of emergence (i.e., > 8 cm for the accessions studied) and by flooding fields as early as possible. The information gained from this study may help design cultural management strategies for weedy rice in Asia.